Johann Christoph Gottscheds Briefwechsel - Historisch-kritische Ausgabe Band 9: November 1742 - Februar 1744 - Gottsched, Johann Christoph (Briefwechsel, 2015)
The highlights of this volume include the celebration of the 200th anniversary of Copernicus`s death. Political developments in Europe remain an important concern for Gottsched. He devotes close attention to the situation of German theater in his correspondence with actors and playwrights. The "literary dispute" with Bodmer and Breitinger becomes ever more heated. Gottsched uses every means available to seek allies in this prolonged controversy.